PERANAN CAMAT DALAM PELAKSANAAN PENGAWASAN KERJA APARATUR PEMERINTAH (Suatu Studi di Distrik Kembu Kabupaten Tolikara) - WEYA, YODIMES (JURNAL ADMINISTRASI PUBLIK, 2016)
Government especially in the environment of the district. The methods used in this study a greater emphasison qualitative research methods. Where this method does not intend to look for a causal result of anythingbut trying to understand the situation and specific background as it is. The results showed the company thatwants to progress and grow of course require supervision, because any trace of the surveillance activitycarried out at the course in an enterprise will not be achieved as expected. One of the supervisory effortsundertaken within the Organization of the district is the oversight on the territory of the District of theOrganization in the field of Kembu necessarily requires the implementation of supervision. Supervisoryefforts is one of the tools of control that is exercised against his leadership.Key words: Role, head of Supervision